The effect of ankle-foot orthoses constrained movements on power output during functional electrical stimulation cycling in paraplegics / Puteri Nur Farhana Hamdan - Puteri Nur Farhana, Hamdan (2017)
Previous research has investigated functional electrical stimulation (FES) cycle power output (PO) from the perspective of knee and hip joint biomechanics. However, ankle-foot biomechanics and, in particular, the effect of releasing the ankle joint on cycle pedal PO during FES cycling in individuals with spinal cord injury (SCI) has not been widely explored. Therefore, the purpose of this study is to determine whether releasing the ankle joint might influence the peak and average pedal PO during FES cycling in individuals with SCI. Seven individuals with motor complete SCI (C5-T11) participated in this study. All participants performed two sessions of FES cycling. For each session, the participants were required to cycle in fixed- and free-ankle setup, in randomized order. There were two stimulation modes of FES cycling for each session. In mode 1, the participants were required to perform FES cycling with the stimulation of the upper leg muscles [quadriceps (QUAD) and hamstrings (HAM)] (known as QH stimulation). In mode 2, the participants were required to perform FES cycling with the stimulation of both upper and lower leg muscles [QUAD, HAM, tibialis anterior (TA), and triceps surae (TS)] (known as QHT stimulation). The peak and average pedal PO of each condition were analyzed. Overall, there was no significant difference in the normalized peak and average pedal PO between fixed- and free-ankle FES cycling for both stimulation modes [F (3, 24) = 0.32, P = 0.81 and F (3, 24) = 1.19, P = 0.33, respectively]. However, the free-ankle FES cycling with QH stimulation contributed to the lowest normalized peak and average pedal POs compared to the other modes of FES cycling (0.66 ± 0.23 and 0.16 ± 0.07 W/W, respectively). The present study revealed that free-ankle FES cycling without the stimulation of shank muscles (TA and TS) caused loss of power during recovery phase of cycling. The power from the hip and knee was lost at the ankle joint, and thus produced low pedal PO. On the other hand, free-ankle FES cycling with QHT stimulation provided greater ankle ROM while preventing power loss from the hip and knee at the ankle joint. The TS muscles stimulation is very important in free-ankle FES cycling to maximize the pedal PO. This finding might serve as a reference for future rehabilitative cycling protocols where both ankle muscle stretching and strength training are the simultaneous aim.